Photocatalysis with solar energy: Sunlight-responsive photocatalyst based on TiO2 loaded on a natural material for wastewater treatment. (October 2016) - Borges, M.E.; Sierra, M.; Cuevas, E.; García, R.D.; Esparza, P.
Highlights: High rate of photocatalysis under solar light. Photocatalysis combining economical and sustainable components including TiO2, black volcanic ashes and solar light. TiO2 nanoparticles loaded on a natural material (black volcanic ashes). Catalyst can absorb both UV and visible light. Photocatalyst in particles for eliminating the complex liquid/powder separation process for wastewater treatment. Abstract: Heterogeneous photocatalysis based on TiO2, as advanced oxidation process, has proven to be an effective application in the removal of aqueous and gaseous pollutants. The use of solar energy to degrade pollutants by photocatalysis represents an economic and sustainable alternative. This research focuses on the photodegradation of pollutants from wastewater by TiO2 nanostructured loaded into a natural mineral material (volcanic soil of black lava). The activity of the photocatalyst was evaluated in different conditions of radiation under sunlight. The results showed that the material is an efficient photocatalyst under visible light, obtaining 95% degradation of wastewater pollutant under sunlight irradiation after only 2 h, and can be proposed for its use in photoreactors for treatment of high-volume of wastewater. The studied material can be used for advanced oxidation treatments in photoreaction systems with continuous flow, thereby resolving the problems arising from the use of conventional powder photocatalytic systems.